PERCEIVED EASE OF USE, PERCEIVED RISK, AND INTENTION TO USE QRIS: A STUDY OF URBAN CONSUMERS IN MEDAN - Liliana, Ola Venina; Munte, Mei Hotma Mariati; Sihombing, Halomoan (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study examines the influence of perceived ease of use and perceived risk on the intention to adopt QRIS (Quick Response Code Indonesian Standard) as a digital payment method among residents of Medan City. With the rapid growth of cashless transactions in Indonesia, understanding consumer adoption behavior is crucial for expanding financial inclusion. A quantitative survey method was employed, collecting primary data from 120 respondents using a structured questionnaire. Convenience sampling was used, and data were analyzed using multiple linear regression through SPSS 26. The results indicate that perceived ease of use has a significant positive effect on adoption intention, confirming the relevance of the Technology Acceptance Model (TAM) in the digital payment context. In contrast, perceived risk was found to have no significant impact, suggesting that users prioritize usability over security concerns when deciding to use QRIS. This implies that ease of access, simplicity of interface, and user experience are more decisive factors than risk perception in driving adoption. The findings highlight the importance for service providers and policymakers to focus on improving platform usability and conducting targeted digital literacy campaigns to accelerate QRIS adoption. This study contributes to the literature on digital finance in emerging economies by empirically validating key behavioral drivers in urban Indonesian consumers.